2022
DOI: 10.1109/access.2022.3174599
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic Detection of Breast Cancer Diagnosis and Prognosis Based on Machine Learning Using Ensemble of Classifiers

Abstract: Breast cancer (BC) is the second most prevalent type of cancer among women leading to death, and its rate of mortality is very high. Its effects will be reduced if diagnosed early. BC's early detection will greatly boost the prognosis and likelihood of recovery, as it may encourage prompt surgical care for patients. It is therefore vital to have a system enabling the healthcare industry to detect breast cancer quickly and accurately. Machine learning (ML) is widely used in breast cancer (BC) pattern classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…We summarize some of the recent machine learning, deep learning, ensemble learning techniques based on the breast cancer classification in Table 1. [2-4, 6, 9, 12, 14, 18, 20, 23, 24, 27-33, 36, 40, 47, 48] or textual datasets [1,5,10,17,21,34,41,42], and the researchers are working on them [1-6, 9, 12, 14, 17, 18, 20, 21, 23, 24, 27-34, 36, 40-42, 47, 48]. The existing works on classification are using the datasets with fewer number of sample images [1, 3, 5, 6, 17, 18, 21, 24, 28-30, 33, 34, 36, 41, 42, 47] that may not sufficient to train deep learning algorithms because training process of a deep learning network require a large amount of image data.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…We summarize some of the recent machine learning, deep learning, ensemble learning techniques based on the breast cancer classification in Table 1. [2-4, 6, 9, 12, 14, 18, 20, 23, 24, 27-33, 36, 40, 47, 48] or textual datasets [1,5,10,17,21,34,41,42], and the researchers are working on them [1-6, 9, 12, 14, 17, 18, 20, 21, 23, 24, 27-34, 36, 40-42, 47, 48]. The existing works on classification are using the datasets with fewer number of sample images [1, 3, 5, 6, 17, 18, 21, 24, 28-30, 33, 34, 36, 41, 42, 47] that may not sufficient to train deep learning algorithms because training process of a deep learning network require a large amount of image data.…”
Section: Related Workmentioning
confidence: 99%
“…The existing works on classification are using the datasets with fewer number of sample images [1, 3, 5, 6, 17, 18, 21, 24, 28-30, 33, 34, 36, 41, 42, 47] that may not sufficient to train deep learning algorithms because training process of a deep learning network require a large amount of image data. The most frequently used datasets are the BreakHis [2,4,6,9,12,14,23,27,31,32,40,48] and the WBCD [1,5,10,17,21,34,41,42]. However, the WBCD dataset consists of only 569 or 699 instances with 32 features, while, the BreakHis dataset consists of 7909 images.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Data science, bioinformatics, statistical genomics, and other fields have all attempted to address this issue. In addition to the aforementioned medical images and genomic data, these apps also allow for the study of organized data [ 29 , 30 ].…”
Section: Related Workmentioning
confidence: 99%
“…Experimental results on WDBC dataset showed that the accuracy of HAW-RP was 98.5%. U. Naseem et al [17] proposed a classifier integration-based breast cancer diagnosis system and automatic prognostic detection system. Experimental results on the WDBC dataset showed that the integrated method outperformed other single methods, with an accuracy of 98.83%.…”
mentioning
confidence: 99%